OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY OF THE MACULA AFTER PLAQUE RADIOTHERAPY OF CHOROIDAL MELANOMA: Comparison of Irradiated Versus Nonirradiated Eyes in 65 Patients. Issue 8 (August 2016) - Shields, Carol L.; Say, Emil Anthony T.; Samara, Wasim A.; Khoo, Chloe T. L.; Mashayekhi, Arman; Shields, Jerry A.
Abstract : Purpose: To study radiation retinopathy after plaque radiotherapy of choroidal melanoma using optical coherence tomography angiography. Methods: Retrospective comparative analysis of 65 consecutive patients with choroidal melanoma, treated with standard dose I-125 plaque radiotherapy and imaged with optical coherence tomography angiography. A comparison of irradiated versus contralateral, nonirradiated (control) eyes was performed. Results: The mean patient age was 55 years. Underlying medical diseases included diabetes mellitus (4/65, 4%) or hypertension (25/65, 38%), but no patient demonstrated disease-related retinopathy. The mean pretreatment melanoma diameter was 11 mm and mean thickness was 5 mm. The mean radiation dose to the foveola was 5663 centiGray. At mean follow-up of 46 months after plaque radiotherapy, the most frequent qualitative finding on optical coherence tomography angiography (irradiated eye) was nonperfusion in the superficial capillary plexus (19/65, 29%) and deep capillary plexus (20/65, 31%), followed by loss of choriocapillaris within tumor margins (11/65, 17%). The quantitative findings revealed foveal avascular zone with significantly larger mean area (irradiated vs. nonirradiated eye) in the superficial plexus (0.961 vs. 0.280 mm 2, P < 0.0001) and deep plexus (1.396 vs. 0.458 mm 2, P < 0.0001), even in eyes without clinical evidence of radiation maculopathy (superficial 0.278 mm 2, P = 0.03; deep 0.454 mm 2, P = 0.02). Parafoveal capillary density (superficial and deep) was decreased in all irradiated eyes ( P < 0.001). This difference was maintained after subgroup analysis of eyes with ( P < 0.001) or without ( P < 0.001) clinical evidence of radiation maculopathy. Mean logMAR visual acuity was significantly reduced in irradiated eyes (0.7 vs. 0.1 [Snellen equivalent 20/100 vs. 20/25], P < 0.001) and the reduced vision was significant even in eyes without clinical evidence of radiation maculopathy (0.4 vs. 0.1 [Snellen equivalent 20/50 vs. 20/25], P < 0.001). Conclusion: Optical coherence tomography angiography demonstrated significant enlargement of the foveal avascular zone and decreased parafoveal capillary density of both superficial and deep capillary plexuses in eyes after plaque radiotherapy of choroidal melanoma, even in eyes with no clinical evidence of radiation maculopathy. Abstract : After plaque radiotherapy of choroidal melanoma, optical coherence tomography angiography demonstrated statistically significant enlargement of superficial and deep foveal avascular zone and reduction in capillary density, even in eyes with no clinical evidence of radiation maculopathy.